Ruddlesden-Popper chalcogenides push the limit of mechanical stiffness and glass-like thermal conductivity in single crystals - Md Shafkat Bin Hoque; Eric R. Hoglund; Boyang Zhao; De-Liang Bao; Hao Zhou; Sandip Thakur; Eric Osei-Agyemang; Khalid Hattar; Ethan A. Scott; Mythili Surendran; John A. Tomko; John T. Gaskins; et al. (Nature Communications)
Abstract Insulating materials featuring ultralow thermal conductivity for diverse applications also require robust mechanical properties. Conventional thinking, however, which correlates strong bonding with high atomic-vibration-mediated heat conduction, led to diverse weakly bonded materials that feature ultralow thermal conductivity and low elastic moduli. One must, therefore, search for strongly-bonded single crystals in which heat transport is impeded by other means. Here, we report intrinsic, glass-like, ultralow thermal conductivity and ultrahigh elastic-modulus/thermal-conductivity ratio in single-crystalline Ruddlesden-Popper Ba n+1Zr n S3n+1, n = 2, 3, which are derivatives of BaZrS3. Their key features are strong anharmonicity and intra-unit-cell rock-salt blocks. The latter produce strongly bonded intrinsic superlattices, impeding heat conduction by broadband reduction of phonon velocities and mean free paths and concomitant strong phonon localization. The present study initiates a paradigm of “mechanically stiff phonon glasses”.